2000
DOI: 10.1038/sj.ijo.0801251
|View full text |Cite
|
Sign up to set email alerts
|

Appetite after weight loss by energy restriction and a low-fat diet–exercise follow-up

Abstract: OBJECTIVE: The aim of the present study was to determine the impact of weight loss on appetite as measured by visual analog scale (VAS). METHODS: Seventeen subjects (10 men and seven women) took part in a 15 week weight loss program which consisted of drug therapy (fen¯uramine 60 mgaday) or placebo coupled to an energy restriction (À2930 kJaday; phase 1) followed by an 18 week low-fat diet ± exercise follow-up (phase 2). Subjects were given a standardized breakfast before and after phase 1 as well as after pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(175 citation statements)
references
References 30 publications
8
161
4
2
Order By: Relevance
“…Heavy, lean sows that do not have sufficiently high lactation intake will likely have poorer longevity due to excessive weight loss. However, weight lossassociated stress can trigger increased appetite to compensate (Doucet et al, 2000) or alternatively inhibit appetite suppression (Ozcan et al, 2009), as shown in other species. Bergsma et al (2008) were the first to coin the term lactation efficiency (LE, defined as output/input), which combines the resources provided by the sow (through weight and fat loss) with lactation intake into an input variable, after accounting for sow maintenance requirements, and relates this input to piglet output.…”
Section: Discussionmentioning
confidence: 97%
“…Heavy, lean sows that do not have sufficiently high lactation intake will likely have poorer longevity due to excessive weight loss. However, weight lossassociated stress can trigger increased appetite to compensate (Doucet et al, 2000) or alternatively inhibit appetite suppression (Ozcan et al, 2009), as shown in other species. Bergsma et al (2008) were the first to coin the term lactation efficiency (LE, defined as output/input), which combines the resources provided by the sow (through weight and fat loss) with lactation intake into an input variable, after accounting for sow maintenance requirements, and relates this input to piglet output.…”
Section: Discussionmentioning
confidence: 97%
“…These differences remained significant when change in body weight was taken into account, suggesting that an adequate intake in vitamins and minerals might influence satiety. Appetite is increased in response to body-weight loss (36,40) due to variations in hormone levels implicated in the regulation of energy balance such as insulin, leptin and cortisol (36,41,42) . Since some vitamins and minerals are involved in the synthesis of these and other peptides and neurotransmitters that control food intake, a decreased micronutrient availability could affect peptide hormone levels and thus interfere with the signalling pathways that control food intake, as was observed in Zn-deprived rats (43) .…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that might thwart adherence is the difficulty in maintaining high levels of dietary restriction in the long term. Also, it has been shown that restrictive diets may have negative effects on eating behaviors such as an increased appetite (Doucet et al, 2000) and an increase in frequency of obsessive thoughts about food (Hart and Chiovari, 1998), and they could also be associated with a greater risk of depression symptoms (Chaput et al, 2007). To avoid the perceived deprivation, an alternative approach could be to emphasize positive messages promoting the consumption of healthy foods with low energy density rather than focusing on restricting high-fat foods.…”
Section: Introductionmentioning
confidence: 99%